(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Prihatiningsih N, Djatmiko HA, Lestari P. 2021. Endophytic bacteria associated with rice roots from suboptimal land as plant growth promoters. Biodiversitas 22: 432-437. Endophytic bacteria directly promoted plant growth and undirectly control the pathogens. This research was aimed to evaluate endophytic bacteria associated with rice root and their activity to promote plant growth and to control rice diseases. The study was conducted at the Laboratorium of Plant Protection and experimental farm Faculty of Agriculture Jenderal Soedirman University, from April to August 2020. The endophytic bacterial from suboptimal land were evaluated for promoting plant growth with soaking seed before seedling and spraying them at 10, 20, and 30 days after transplanting. The experiment was arranged with six replications and four treatments namely control (untreated endophytic bacteria) SM1 (endophytic bacteria isolate from Somagede); SB1 and SB3 (from Sumbang). Xanthomonas oyzae pv. oryzae was nature inoculation because the experiment location is in the endemic category of bacterial leaf blight. The variables observed were the plant growth components i.e plant height, number of tillers, number of panicles, incubation period, disease intensity, infection rate and effectiveness control. The result of this research shows that endophytic bacteria from Somagede (SM1) is the best to enhance plant height and number of tillers, and suppress disease intensity, and delay of incubation period.